Imidazoquines as Antimalarial and Antipneumocystis Agents - Vale, Nuno (2015)
Peptidomimetic imidazolidin-4-one derivatives of primaquine (imidazoquines) recently displayed in vitro activity against blood schizonts of a chloroquine-resistant strain of Plasmodium falciparum. Preliminary studies with a subset of such imidazoquines showed them to both block transmission of P. berghei malaria front mouse to mosquito and be highly stable toward hydrolysis at physiological conditions. This prompted Lis to have deeper insight into the activity of imidazoquines against both Plasmodia and Pneumocystis carinii, on which primaquine is also active. Full assessment of the in vivo transmission-blocking activity of imidazoquines, in vitro tissue-schizontocidal activity on P. berghei-infected hepatocytes, and in vitro anti-P. carinii activity is now reported. All compounds were active in these biological assays, with generally lower activity than the parent drug. However, imidazoquines' stability against both oxidative deamination and proteolytic degradation suggest that they will probably have higher oral bioavailability and lower hematotoxicity than primaquine, which might translate into higher therapeutic indexes.. - Fundacao para a Ciencia e a Tecnologia [PTDC/QUI/65142/2006, CONC-REEQ/275/QUI, REDE/1517/RMN/2005, PTDC-BIA-BCM-71920-2006, SFRH/BPD/4834572008]; CIQUP ; CECF ; Portuguese Ministry of Science ; Howard Hughes Medical Institute International Scholar ; Doris Duke Charitable Foundation. - This work was mainly supported by Fundacao para a Ciencia e a Tecnologia (FCT, Portugal) through projects PTDC/QUI/65142/2006, CONC-REEQ/275/QUI, REDE/1517/RMN/2005 to P.G. and PTDC-BIA-BCM-71920-2006 to M.P. N.V. thanks FCT for postdoctoral grant SFRH/BPD/4834572008. P.G. and R.M. thank FCT for financial support to CIQUP and CECF research units, respectively. M.P. is it holder of a Ciencia 2007 position of the Portuguese Ministry of Science. M.M.M. is a Howard Hughes Medical Institute International Scholar. P.J.R. was supported by grants from the National Institutes of Health and Medicines for Malaria Venture and is a Distinguished Clinical Scientist of the Doris Duke Charitable Foundation.